Moderasi Beragama bagi Minoritas Muslim Etnis Tionghoa di Kota Makassar - Ramli, Ramli (LPPM IAIN Parepare, 2019)
The results of this study indicate that religious moderation for the ethnic Chinese Muslim minority in Makassar City includes: (a) Chinese ethnic in Makassar, both those who have embraced Islam as their religious teachings, and the non-Muslim Chinese are long-lived communities in Makassar city. Its existence as a minority has become an inseparable part of religious life that lives in harmony and peace. (b) For the ethnic Chinese Muslim minority community in the city of Makassar, a good relationship has been established between the subject and object in every religious activity, both different, as well as the same ethnic, religious and cultural backgrounds. (c) The development of religious moderation involves all existing components and potentials, with cultural and religious considerations related to the implementers, material, methods, media and targets, as well as various elements involved in the process of enhancing the knowledge, understanding and implementation of peaceful religious teachings, polite and tolerant for the minority of ethnic Chinese Muslims in the city of Makassar, using the basic concepts of moderate religion (wasatiyah) both from the Koran, and in as-Sunnah.